Better Students Ask More Questions.
Given f(x)=2x^2-5 and g(x)=4-2x, find (f of g)(x).
1 Answer | add yours
High School Teacher
`f(x) = 2x^2 - 5` and `g(x) = 4-2x` substitute g(x) for every value of x in f(x)
`therefore` (f of g)x can be written as:
f(g(x))= `2(4-2x)^2 - 5`
= `2(16 - 16x + 4x^2) -5`
= `32- 32x +8x^2 -5`
= `8x^2 -32x + 27`
Posted by durbanville on November 8, 2012 at 5:41 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.